Synthesis and catalytic activity of monodisperse gold-mesoporous silica core-shell nanocatalysts - Sekhar, A. C. Sunil; Meera, C. J.; Kottavarithottil Ziyad; Gopinath, Chinnakonda S.; Vinod, C. P. (Catalysis Science & Technology, 2013)
Core-shell nanostructures, where gold nanoparticles of sub 10 nm size are successfully encapsulated inside porous silica spheres, have been prepared. The detailed characterization of the catalyst shows a high surface area and good mesoporosity. The sinter resistance of the catalyst under repeated cycles of the CO oxidation reaction is observed.

Activity enhancement upon the incorporation of titanium: au@ti-sio2 core-shell nanocatalysts for the CO oxidation reaction - Sekhar, Anandakumari C. Sunil; Kottavarithottil Ziyad; Soni, Yogita; Vinod, Chathakudath P. (ChemCatChem, 2015)
The encapsulation of gold nanoparticles 8-12nm in size within a porous Ti-SiO2 shell to form a core-shell nanoarchitecture was investigated, and the catalytic activity of the resulting structure was probed. Detailed characterization of the synthesized materials shows that the core-shell morphology is lost beyond a certain amount of incorporated titanium, and results in normal gold-supported Ti-SiO2. The material has a high surface area (913m(2)g(-1)) and high porosity, both of which make it an excellent choice for catalytic applications. With the optimum amount of incorporated Ti, the core-shell catalyst shows excellent room-temperature CO oxidation activity over several cycles with retention of its morphology at higher temperatures.
Keywords: core-shell structures; gold nanoparticles; Oxidation; Ti-SiO2